Integrating generative AI with the flipped classroom teaching model: enhancing emotional well-being and student achievement - Hanchu Liu; Kanyarat Sriwisathiyakun; Sirirat Petsangsri (Cogent Education, 2026)
Education in the modern society is undergoing rapid transformation as helping students perform better academically and feel emotionally better has become increasingly important. One way to support this is by using Generative AI (GenAI) in combination with the flipped classroom approach. This study focused on creating and testing a new teaching model called the Generative AI-Integrated Flipped Classroom (GenAI-FC) designed for mental health courses. The research was done in two main parts. In the first part, the GenAI-FC model was developed and its structure was adjusted based on feedback from experts. In the second part, the model was used with students to see how it affected their learning and emotional well-being. The results were promising as five experts reviewed the model and gave it a high-quality score of 4.68 out of 5, showing that it was strong and useful for teaching. Then, the model was tested with 95 first-year university students. After using the model, students showed clear improvement in their exam scores and emotional well-being, based on a standard questionnaire. Both scores were significantly higher after the course compared to before as the results show that the GenAI-FC model can make a real difference by helping students to learn better and also feel more supported. This suggests that using Generative AI in a flipped classroom could be a helpful way to improve education and support students’ mental health at the same time.
Keywords: Innovative Teaching Methods; Neuroscience, Education and Cognitive Function; Emotional Intelligence and Performance